Effectiveness of an Automated Feedback System on Creative Writing and Scientific Translation Skills Among Undergraduate Students: A Quasi-Experimental Study - Danila Adi Sanjaya; Gayatri Putri (Enigma in Education, 2026)
This quasi-experimental study investigates the effectiveness of an automated feedback system (AFS) on creative writing skills (CWS), scientific translation skills (STS), and writing self-efficacy (WSE) among undergraduate students. Participants comprised 136 students (experimental group: n = 68; control group: n = 68) from the Department of English Education at a public university in Palembang, Indonesia, enrolled in Writing and Translation courses during a 10-week intervention period. The experimental group received automated feedback through an integrated computer-assisted language learning platform, while the control group received conventional instructor-provided feedback. Pre- and post-test data were analyzed using Analysis of Covariance (ANCOVA), with large effect sizes observed across all dependent variables: creative writing skills (d = 1.84, 95% CI [1.38, 2.30], p < 0.001); scientific translation skills (d = 2.08, 95% CI [1.62, 2.54], p < 0.001); and writing self-efficacy (d = 1.94, 95% CI [1.49, 2.39], p < 0.001). Results demonstrate that automated feedback systems significantly enhance both skill development and learner confidence in academic writing contexts, particularly for skill-intensive tasks requiring iterative practice. The study also underscores the importance of combining automated feedback with periodic instructor guidance and peer collaboration.